Survey-Based Qualitative Analysis of Young Generation Perception of Sustainable Development in Poland (Agricultural Engineering, 2020)
Understanding the perception of Sustainable Development can help to identify misconceptions surrounding the concept in order to design better education plans and public policies on this subject. Evaluating the perception of sustainability issues by focusing on the young generation as is an important proxy to imagine what the future holds for in terms of addressing sustainable development. We conducted 177 in-person interviews on a heterogeneous group of students and random volunteers in four cities in Poland to assess their perception of Sustainable Development. The vast majority (89.3%) of the respondents were familiar with the term ‘Sustainable Development’. However, part of them (57%) associated it only to the human and social development dimensions and its institutions, whereas 17.5% related it with its environmental aspects. The results supported by the literature review highlight challenges concerning the path towards a comprehensive perception of Sustainable Development and hence the achievement of the SDGs. Based on these results, we identify opportunities and incentives to bring Poland towards 2030 Agenda.